Nature of the magnetism of iridium in the double perovskite Sr2CoIrO6 - Agrestini, Stefano; Haverkort, Maurits W. (Physical review, 2019)
We report on our investigation on the magnetism of the iridate double perovskite Sr2CoIrO6, a nominally Ir5+ Van Vleck Jeff=0 system. Using x-ray absorption (XAS) and x-ray magnetic circular dichroism (XMCD) spectroscopy at the Ir-L2,3 edges, we found a nearly zero orbital contribution to the magnetic moment and thus an apparent breakdown of the Jeff=0 ground state. By carrying out also XAS and XMCD experiments at the Co-L2,3 edges and by performing detailed full atomic multiplet calculations to simulate all spectra, we discovered that the compound consists of about 90% Ir5+ (Jeff=0) and Co3+ (S=2) and 10% Ir6+ (S=3/2) and Co2+ (S=3/2). The magnetic signal of this minority Ir6+ component is almost equally as strong as that of the main Ir5+ component. We infer that there is a competition between the Ir5+−Co3+ and the Ir6+−Co2+ configurations in this stoichiometric compound.